2019
DOI: 10.1371/journal.pone.0221280
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of maternal health care and birth outcome in the Dande Health and Demographic Surveillance System area, Angola

Abstract: Objectives Maternal health care improvement and reduction of maternal and child mortality are priorities of the global health agenda. In Angola, maternal mortality remains high and the risk of pregnancy-related death was 1 in 32 during 2015. This study aims to identify demographic and social factors influencing antenatal care and health facility delivery among women in Dande and to understand their impact on birth outcomes. Methods This study is based on community–based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 50 publications
4
56
0
Order By: Relevance
“…The odds of having at least four ANC visits during pregnancy was significantly lower among women who were not married. Studies have shown that both economic status and dynamics regarding the distribution of power influence the use of maternal health services [64]. High birth order was also associated with a lower likelihood of utilising ANC4.…”
Section: Discussionmentioning
confidence: 99%
“…The odds of having at least four ANC visits during pregnancy was significantly lower among women who were not married. Studies have shown that both economic status and dynamics regarding the distribution of power influence the use of maternal health services [64]. High birth order was also associated with a lower likelihood of utilising ANC4.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few reports about ANC in Angola. [3][4][5] To our knowledge, this is the first one about ANC infection screening. We characterised ANC screening rates for HIV, HBV and syphilis among 500 parturient women admitted between October 2016 to September 2017 to the Irene Neto Maternity service in Lubango, Huíla, the second most populous province of Angola (Oliveira et al, 2020, accepted to Sex Transm Infect).…”
Section: Hiv Hbv and Syphilis Screening In Antenatal Care In Lubangomentioning
confidence: 99%
“…Studies conducted by a number of scholars in Africa have identified socio-economic factors such as maternal education, household wealth status, sub-national region, and place of residence as predictors of the utilization of ANC services [13][14][15][16][17][18][19]. Literature in Angola show maternal health service, including ANC, can be affected by socio-economic factors such as maternal education, maternal age, household economic status, place of residence, distance to facility, parity and previous adverse pregnancy outcomes [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…There is little evidence in Angola about determinants of utilization of ANC services [20,21] and the extent of socio-economic and geographically related inequalities are largely unknown. Context-based evidence is necessary to provide targeted interventions that reduce health inequities among sub-groups [27].…”
Section: Introductionmentioning
confidence: 99%